Endovascular therapy versus medical management in isolated anterior cerebral artery acute ischemic stroke: a multinational multicenter propensity score-weighted study - Salim, Hamza; Pulli, Benjamin; Yedavalli, Vivek; Milhem, Fathi; Musmar, Basel; Adeeb, Nimer; Lakhani, Dhairya A.; Essibayi, Muhammed Amir; Heit, Jeremy Josef; Faizy, Tobias D.; Naamani, Kareem El; Henninger, Nils; et al. (Journal of neuroInterventional surgery, 2025)
Background Isolated anterior cerebral artery occlusions (ACAo) in patients with acute ischemic stroke present significant challenges due to their rarity. The efficacy and safety of endovascular therapy (EVT) in comparison with best medical therapy (BMT) for ACAo remains unclear. This study aimed to assess the outcomes of these treatments. - Methods This multinational, multicenter study analyzed data from the MAD-MT registry. Data were collected retrospectively from 37 sites across North America, Asia, and Europe. Inverse probability of treatment weighting (IPTW) was applied to balance confounding variables. The primary outcome was functional independence (modified Rankin Scale (mRS) scores of 0-2) at 90 days. Secondary outcomes included excellent outcomes (mRS 0-1), mortality at 90 days, and NIH Stroke Scale (NIHSS) score on day 1 post treatment. - Results Of the 108 patients, 36 received BMT and 72 underwent EVT. The median age was 75 years, and 56% were male. At 90 days, 40% of patients achieved mRS 0-2, with no significant difference between EVT and BMT (38% vs 45%, p=0.46). Procedural success (mTICI 2b-3) was 91% in the EVT group, with a sICH rate of 2.9%. IPTW-adjusted analysis showed no significant difference between EVT and BMT for functional independence (OR 1.17, 95% CI 0.23 to 6.02, p=0.85), mortality (25% vs 21%, p=0.71) or day 1 NIHSS scores (Beta 2.2, 95% CI −0.51 to 4.8, p=0.11). - Conclusions EVT showed high procedural success but did not significantly improve functional outcomes or mortality compared with BMT in patients with ACAo. Further randomized trials are needed to clarify EVT’s role in ACAo.